Pregnancy after breast cancer treatment in young patients - Lee, Young-Jin; Yoo, Tae-Kyung; Lee, Sae Byul; Kim, Jisun; Chung, Il-Yong; Ko, Beom Seok; Lee, Jong Won; Son, Byung Ho; Kim, Seonok; Kim, Hee Jeong (Frontiers in Oncology, 2025)
IntroductionBreast cancer (BC) treatments can impair fertility in young women, causing considerable distress and potentially influencing treatment decisions, yet comprehensive real-world data on pregnancy outcomes after BC remain limited. This study aims to provide comprehensive real-world data on pregnancy following BC treatment to guide clinical practice and patient counseling.MethodsWe conducted a retrospective cohort study using medical records from a single tertiary medical center in South Korea. The study included 995 premenopausal women aged 18 to 40 years who were diagnosed with stage 0–III BC between December 2010 and September 2020. The primary outcomes included post-treatment pregnancy rates, factors associated with subsequent pregnancy, timing of conception, pregnancy outcomes, and oncologic outcomes among those who conceived.ResultsThe median age was 32 years (interquartile range [IQR], 30–34 years). Of 995 patients, 115 had at least one pregnancy after their BC diagnosis. Significant differences in pregnancy rates and the interval from BC treatment to pregnancy were observed according to hormone receptor status and pregnancy history prior to BC diagnosis. Among those who conceived, 46.1% discontinued endocrine therapy (ET) to achieve pregnancy. Following BC treatment, pregnancies were observed in 7.8% of women who were >35 years old at diagnosis, 17.8% of women who were unmarried at diagnosis, and 6.8% of women who already had children. Of the 76 patients who discontinued ET to attempt pregnancy, 53 (69.7%) successfully conceived. Among those who achieved pregnancy after ET discontinuation, four patients (7.5%) experienced cancer recurrence.DiscussionEffective fertility preservation counseling is necessary for patients of reproductive age with BC, regardless of age, marital status, or whether they had children before BC diagnosis. This study can be referenced to appropriately address and manage the impact of chemotherapy and ET on pregnancy after BC treatment.